Plankton Biodiversity in The Burai River of Ogan Ilir District, Sumatera Selatan - Awalul Fatiqin (Universitas Islam Negeri Mataram, 2019)
The purpose of this study was to determine the abundance of plankton in the Ogan Ilir regency of South Sumatra. Samples were obtained using a purposive random sampling method with plankton as the main material for measuring abundance and the Shannon Wiener Diversity Index (H), Simpson Dominance Index (C), and plankton abundance index. The results of the study obtained six classes consisting of 15 genera of plankton including Fragielaria, Synedra, Eunotia, Diatom, Fustulia, Oedogonium, Gonium, Chaetophora, Microspora, Allona, Neuplius, Lyngbya, Spirulina, Cyclotella and Dismidium. Diversity value at point 1 (1.75) with medium category, point 2 (3.5) with high category, point 3 (0.75) with the medium category. The diversity value of three points is known to be low in population.